Pentingnya peran kader kesehatan pelayanan kesehatan di Posyandu - Sugeng Riyadi; Ulfah Agus Sukrillah; Welas Haryati (Prodi Keperawatan Purwokerto, 2019)
Background: One of promotive health effort to realize desa siaga is by revitalizing posyandu (Dinkes Prop Jateng, 2007). In Holding posyandu, cadres take an important role whether in all plans of posyandu preparation activities or in applying five tables system activities.There are 75 posyandu in working area of Puskesmas Leyangan ang kalongan and the level of program achievement is at about 68%(51 posyandu ), still in the category of unsteady posyandu that one of indicators is minimum role of cadres (active cadres is less than 5 people for each posyandu and the execution of posyandu is less than 8 time in one year and just 8% belongs to purnama category then in 2008 increase becoming 20,3%. But this number is still under SPM 2010 target at about 40%.Metode: This purpose of this research is to know the factors that influence the lack of cadres participation in posyandu activities in working area of Puskesmas Leyangan and Kalongan..Whereas the sample is inactive cadres whose presents are less than 6 time in the latest one year. The analysis technique is using content analysis. In analysis data, researchers need full focus, the movement of power, physical and mind.Result: Characteristic of respondents age is between 35 years up to 40 years. The level of education is almost all primary school. Most of them have good knowledge about posyandu. Respondent attitude shows that the execution of posyandu, said that working is more important for them and most of them said that facilities in posyandu are not complete.Conclusion: The support of husbands is still lack, whereas the support from the chief still lack. Most of respondents get support from health provider, especially from local midwives